Respon gulma dan tanaman akasia terhadap aplikasi herbisida pra tumbuh - Afrizal, Jeri; Harun, M. Umar; Marlina (Holistic: Journal of Tropical Agriculture Sciences, 2023)
The study aims to know active ingredients and a dose of pre-emergence herbicides for suppressing weeds growth and it’s the effect on juvenile acacia three months after plant-ing. The study was conducted in PT. Bumi Andalas Permai, The Sugihan Water District, Patch G 3020, The Baung River, Ogan Komering Ilir, South Sumatra. The study used a Randomized Block Design (RBD) and 8 treatments. Without Pre-Emergence Herbicides (T1), Isoxaflutole 150 g․ha-1 (T2), Flumioxazine 100 g․ha-1 (T3), Flumioxazine 200 g․ha-1 (T4), Indaziflame and Iodosulfuron 150 g․ha-1 (T5), Indaziflame and Iodosulfuron 250 g․ha-1 (T6), Sulfentrazon 500 ml․ha-1 (T7), and Sulfentrazon 750 ml․ha-1 (T8). Research started from October 2021 to January 2022. The results showed that the dosed and var-ious of pre-emergence herbicides a significant effect for weeds covered, Specific Leaf Area (SLA) 8, and 12 weeks after application. However, herbicides dit not effect for height and diameter acacia stems. The best treatment to suppress for weed growth was at Indazi-flame and Iodosulfuron 250 g․ha-1, a total weed cover of 8,06 % and dominated by the narrow leave Ottochloa nodosa with SDR value of 78,47 %. The biggest increase for height and diameter of acacia stems was for the active ingredient Sulfentrazon 750 ml. ha-1 which 107,56 cm and a diameter stem 3,62 cm. Highest value for Specific Leaf Area was at a treatment of Control with 119,37 cm².g-1. Treatment of Isoxaflutole 150 g․ha-1 caused a dechlorophyllization effect of acacia leaves with percentage injury of plant to the active ingredient Isoxaflutole is 44,79 %.